(untitled) (Research, Society and Development, 2023)
There is a demand for new microorganisms with the potential to degrade recalcitrant petroleum compounds, such as polycyclic aromatic hydrocarbons (PAHs). The objective of this research was to evaluate the potential of the AM15 strain isolated from water samples from the effluent dike of the Urucu petroleum Province, to degrade a mixture of PAHs. After isolation in culture medium, and initial screening by Gram stain, it was found to be yeast. The characterization of the strain was carried out by analysis based on the sequences of the polymorphic regions ITS1/ITS2 and D1/D2 of the 28S rRNA gene, concomitant with the restriction fragment size polymorphism, generated by the Polymerase Chain Reaction-Fragment Length Polymorphism of Restriction (PCR-RFLP). The ability of yeast to degrade petroleum compounds was determined by testing with the redox indicator 2,6-Dichlorophenol Indophenol (DCPIP), and degradation was confirmed and quantified by gas chromatography and mass spectrometry (GC-MS) analyses. Molecular analyzes indicated that the AM15 strain belongs to the Diutina mesorugosa species. The results obtained in the test carried out with DCPIP showed that the AM15 strain has the potential to degrade hydrocarbons present in petroleum and diesel oil. GC-MS analyzes confirmed that the AM15 strain was able to degrade 79.4% of a mixture of PAHs in 21 days. These results suggest that D. mesorugosa AM15 is promising to degrade different types of hydrocarbons, and can be used as a tool in the bioremediation of oil-impacted areas.